The Anatomy of the Transmission of Macroprudential Policies - Acharya, Viral (IMF Working Papers; Working Paper ;, 2020)
We analyze how regulatory constraints on household leverage-in the form of loan-to-income and loan-to-value limits-affect residential mortgage credit and house prices as well as other asset classes not directly targeted by the limits. Supervisory loan level data suggest that mortgage credit is reallocated from low-to high-income borrowers and from urban to rural counties. This reallocation weakens the feedback loop between credit and house prices and slows down house price growth in "hot" housing markets. Consistent with constrained lenders adjusting their portfolio choice, more-affected banks drive this reallocation and substitute their risk-taking into holdings of securities and corporate credit.